Histopathological Investigation on Puntius sophore (Hamilton) Affected by Epizootic Ulcerative Syndrome - Ira, Akshita; Agrahari, Pooja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Histopathological investigation of Puntius sophore (commonly known as the pool barb) affected by Epizootic Ulcerative Syndrome (EUS) would typically reveal a range of pathological changes in the tissues, particularly in the skin, muscle, and internal organs. EUS is a disease caused by the Oomycete Aphanomyces invadans, which leads to severe ulcerative lesions in fish. The histological analysis of the afflicted P. sophore was the main aim of this investigation. During the study period, the putative fungus was detected from 228 EUS-infected fish samples using established techniques for isolation, culture, and identification. The EUS outbreak was visible in the muscle, liver, and kidney sections of infected fish samples. Granulomatous and inflammatory tissues replaced underlying muscles whereas the epidermis is completely lost.